2018
DOI: 10.1186/s40942-018-0144-9
|View full text |Cite
|
Sign up to set email alerts
|

Central subfield thickness and cube average thickness as bioimaging biomarkers for ellipsoid zone disruption in diabetic retinopathy

Abstract: BackgroundTo evaluate the association of central subfield thickness (CST) and cube average thickness (CAT) with ellipsoid zone (EZ) disruption on spectral domain optical coherence tomography (SD-OCT) in patients of diabetic retinopathy (DR).MethodsCross sectional study including consecutive patients of type 2 diabetes mellitus [without DR (No DR, n = 97); non-proliferative DR (NPDR, n = 91); proliferative DR (PDR, n = 83)] and healthy controls (n = 82) was undertaken. CST and CAT values were measured using SD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…11 Early change in DRIL prospectively identifies eyes with a high probability of subsequent VA improvement or decline. Disruption of the ellipsoid zone (EZ) has been found to be associated with a decrease in VA. [12][13][14][15][16][17] RPE topographic alterations have been found to be associated with a decrease in VA and EZ disruption. [18][19][20][21] The present study was undertaken to evaluate the correlation of serum vitamin D levels with central subfield thickness (CST), cube average thickness (CAT), DRIL, EZ disruptions and RPE topographic alterations, for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…11 Early change in DRIL prospectively identifies eyes with a high probability of subsequent VA improvement or decline. Disruption of the ellipsoid zone (EZ) has been found to be associated with a decrease in VA. [12][13][14][15][16][17] RPE topographic alterations have been found to be associated with a decrease in VA and EZ disruption. [18][19][20][21] The present study was undertaken to evaluate the correlation of serum vitamin D levels with central subfield thickness (CST), cube average thickness (CAT), DRIL, EZ disruptions and RPE topographic alterations, for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the close correlation between retinal vascular abnormalities and DR severity, 5,6 and quantitative vascular features of nonproliferative DR (NPDR) have been validated for computer-aided DR staging. 7,8 Recent studies have also reported early retinal neurodegeneration in DR. [9][10][11] Moreover, electrophysiologic features have provided evidence for photoreceptor changes in patients with DR, 12,13 suggesting that outer retinal alterations may be observed in optical coherence tomography (OCT).…”
mentioning
confidence: 99%